An Elixir for Development? Olive Oil Policies and Poverty Alleviation in the Middle East and North Africa. (5th August 2013) - Lybbert, Travis J.; Elabed, Ghada
Abstract : The evolution of olive oil markets has sparked interest in policies that promote olive oil as a means of inducing rural development across the Middle East and North Africa. This article describes policies that link olive oil markets to rural development in Morocco, Syria and Tunisia and evaluate their effectiveness. It uses a framework that combines producer heterogeneity and market differentiation to describe how rural poverty impacts will be shaped by production, quality and marketing constraints. While the flow of olive oil from producers to the market may have increased, that of information and incentives in the reverse direction is still limited, something that too few olive oil policies aim to improve.